Analisis Putusan Hakim Terhadap Kasus Perlindungan Konsumen Bidang Perumahan dengan Sistem Syariah di Pengadilan Agama Bukittinggi (Studi Kasus Putusan Pengadilan Agama Bukittinggi Perkara Nomor: 604/Pdt.G/2020/PA. Bkt) - Nur Idris, Muhammad; Azheri, Busyra; Rembrand, Rembrand (UNES Law Review, 2023)
The aim of conducting research on Consumer Legal Protection in the Housing Sector in the City of Bukittinggi is as follows: 1. To find out the basic principles of Consumer Legal Protection in the Housing Sector using the Sharia System in the Event of Default by One of the Parties. 2. To find out the Judge's Decision on Consumer Legal Protection Cases in the Housing Sector with the Sharia System. In the research, the author took an empirical, descriptive, juridical approach. From the results of this research it is known that: 1. Indonesia as a country of law, legislation has provided the basis for legal protection for consumers. where the government guarantees legal certainty to protect citizens. In this case of default, the consumer as a buyer of one of the housing units has been harmed by the developer and has filed a lawsuit in the Religious Court. This is by the law where legal action can be taken if a default in the agreement occurs. the other is by filing a lawsuit in court. 2. Judge's Decision on Consumer Legal Protection Cases in the Housing Sector. In this decision, the opponent's application was rejected by the judge because he did not have proof of ownership of the land and house in the form of a certificate. However, in giving this decision, according to researchers, the judge did not give the maximum decision